Development of SPAM Network in Huta Padang Village, Bandar Pasir Mandoge District - Ahmad Ridho Siagian; Abdi Sugiarto; Cut Nuraini (Journal of Information Technology, computer science and Electrical Engineering, 2025)
This study aims to research the development of SPAM networks in Huta Padang Village, Bandar Pasir MandogeDistrict. This study uses a qualitative approach, which aims to understand the phenomenon of the developmentof the Drinking Water Supply System (SPAM) network in Huta Padang Village, Bandar Pasir Mandoge District.This research is included in the type of qualitative descriptive research. The location of this research was carriedout in Huta Padang Village, Bandar Pasir Mandoge District, which is a remote area with challenges in accessingclean water. The data collection techniques in this study include: In-depth Interviews The researcher conductedsemi-structured interviews with key sources. Overall, the development of the SPAM network in Huta PadangVillage has brought significant and positive changes to the community. Through improving access to clean water,health, economy, and social welfare, this project is an important step in supporting sustainable development inthe village. Continuing and expanding initiatives like this will further contribute to the progress of society in thefuture.